EFEKTIVITAS PENERAPAN MEDIA PEMBELAJARAN FISIKA BERBASIS AUGMENTED REALITY: STUDI LITERATUR - Socrates, Tegar Putra; Mufit, Fatni (EduFisika: Jurnal Pendidikan Fisika, 2022)
This study aims to describe the effectiveness of the application of augmented reality-based learning media in physics learning. This effectiveness is in terms of increasing understanding of concepts, interest in learning, learning outcomes, and students' critical thinking skills. This research is due to the lack of understanding of physics by students at various levels of education. Learning physics is considered difficult because of the abstract concept and the lack of innovation in learning so that it affects the ability of students. Therefore, we need an innovation in the physics learning process in the form of augmented reality-based learning media. Quantitative approach is the approach used in this research and literature study as a data collection method. The literature sources used are from the indexing portals Google Scholar, Sinta, Garuda and others. Researchers obtained 10 references related to study objectives from 2014 to 2022. From the analysis of the literature study conducted, it was found that the use of augmented reality in learning physics can increase conceptual understanding, increase interest in learning, and improve students' critical thinking skills in learning physics.